Social media, religion and shifting boundaries in globalizing China. Issue 3 (September 2020) - Lim, Francis KG; Sng, Bee Bee
This article examines how Chinese Christians utilize social media to forge online communities and how religion is integrated into believers' daily lives using the concept of intercontextuality. The intercontextuality of online communication enables Chinese Christian users to communicate about their daily routines and Christian values on a regular basis, thus allowing them to align their Christian concerns with wider social issues. At the same time, Christian users of social media are cognizant and wary of the highly restrictive political context of China. They often maintain a boundary between the 'religious' and the 'political', thus avoiding attracting the unwanted attention of the authorities. The article concludes with some reflections on the political implication of the study's findings.